Peran Polisi Kehutanan dalam Perlindungan Satwa Liar (Studi Kasus di Balai Konservasi Sumber Daya Alam Bali) - Komang Gede Pramantara; I Made Minggu Widyantara; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2022)
Irresponsible actions that can cause damage to nature reserves and conservation areas where there is rampant hunting of protected wildlife that can damage the ecosystem. Forestry Police at the Natural Resources Conservation Center as law enforcers who have the duty and authority to protect and implement forest, plant and animal security. The purpose of this research is to address the causes of wildlife violations in Bali's natural resource conservation areas, as well as to find out how the role of the forest police from the Bali Natural Resources Conservation Center is in protecting wildlife in Bali's natural resource conservation areas. The research uses empirical research methods using a sociological juridical approach. The form of data used is Primary, Secondary, and Tertiary data. To find out the results in this study, data analysis using qualitative methods. The results of this study indicate that the Forestry Police who are at the Bali BKSDA carry out patrols and monitoring in nature, protect the community, install warning boards, make captive areas, coordinate with related agencies and carry out socialization.